E-Cigarette Chemistry and Analytical Detection - Strongin, Robert M. (Annu Rev Anal Chem (Palo Alto Calif), 2019)
The study of e-cigarette aerosol properties can inform public health while longer-term epidemiological investigations are ongoing. The determination of aerosol levels of known toxins, as well as of molecules with unknown inhalation toxicity profiles, affords specific information for estimating the risks of e-cigarettes and for uncovering areas that should be prioritized for further investigation.